Sistema de gestão ambiental em estações de tratamento de esgoto. O caso da ETE Remédios (Salesópolis - SP) - Ramos, Andréia Guaracho (2004)
The sanitation companies have as mission the supply of services of basic sanitation, especially the water supply of good quality for the suppliment of the necessities of domestic and industrial supplying, as well as the collection, treatment and final disposal of the generated sewers, to guarantee the conditions of public health for all the population of its area of performance and to contribute for the ambient quality. These commitments, fort I appeal ambient, can be strengthened, with the implement of a System of Ambient Management and with the formularization of the Ambient Politics of the organization. The deficiency of collecting nets of sewer, added to the situation that 10% of the total sewer are only dealt with, in Brazil (IBGE, 2000), evidences the bad management of these systems, that still is aggravated to the situation of that exactly these 10% are not ambiently correct. The stations of treatment of sewer, any that is the adopted process, have industrial characteristics using raw material; input; generating waste and needing prepared human resources for the performance of its activities and that many times are not attempting against for this. Inside of this scene, the option for the adoption of a System of Ambient Management appears, that besides being a way for the preservation of the nature and the man; through the prevention of the pollution; it offers the half ones for the reduction of wastefulnesses, reduction of costs and promotion of the continuous improvement of the processes and products. The main objective of this work is; through a case study, being the applied methodology; to analyze the contributions of a System of Ambient Management in a Station of Treatment of Sewer. For this, the stages of implantation of the SGA were analyzed, where if it verifies the necessary requirements for the implantation of NBR ISO 14001. Through this analysis one concludes that the certification of conformity with NBR ISO 14001, does not guarantee the ambient quality, however, a systemize System of Ambient Management contributes for a management capable to alert and to visualize as the activities of a Station of Treatment of Sewer can exert negative interferences on the environment and become these sustainable activities ambiently.